Short-term effect of alginate-biochar microbeads in corn germination - Domingues, Murilo T. [UNESP]; Bueno, Carolina de Castro [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Loyola-Licea, Juan C; Rosa, André Henrique [UNESP] (My University, 2014)
Biochar is the solid by-product of biomass pyrolysis. It is a promising soil conditioner and can be a material with high aggregate economic value, since its performance can improve plant’s nutrient utilization and reduce the usage of conventional fertilizers. Biochar can be used in the formulation of new types of fertilizers as polymeric microbeads. These microbeads can be enriched with biochar and nutrients in its matrix to form fertilizers of slow release of nutrients. Thus, as a promising agricultural material, it is important to assess the environmental hazards caused by the implementation of these microbeads. In this context, seeds were sown in a soil-less Petri dish with microbeads produced with biochar from sugarcane enriched with or without phosphate. The seeds germination and its vitality were evaluated by the first germination count (FGC) and the germination speed index (GSI). The short-term effects showed that the microbeads, in general, assessed by the means of FGC, GSI and mass gain showed the best performance, suggesting that the environment created by these materials provided the best chemical and physical interaction with the embryonic axes.
Keywords: biochar; germinação; microesferas